2000
DOI: 10.1080/00071660050022317
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of protein synthesis to refeeding in various muscles of fasted chicks

Abstract: 1. The change in the rate of protein synthesis of different muscles, concentrations of plasma insulin, plasma insulin-like growth factor-I (IGF-I) and other plasma components were investigated after refeeding in fasted chicks. 5.2 g of the complete diet was refed. This was the maximum that could be force-fed with water. 2. The fractional synthesis rates (FSR) of breast (M. pectoralis major) and leg (M. gastrocnemius) muscles were measured after injection of L-[2, 6-(3)H]phenylalanine. Plasma insulin and IGF-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 19 publications
3
16
0
1
Order By: Relevance
“…Total plasma proteins are a common parameter utilized to estimate the avian body condition. Moreover, albumin, one of the main serum proteins, serves as the most favorable source of amino acids for synthesis of tissue proteins [30]. Similar total protein and albumin content in the blood of all the treatment groups in our study represented normal body condition of all the experimental groups.…”
Section: Blood Biochemical Parametersmentioning
confidence: 53%
“…Total plasma proteins are a common parameter utilized to estimate the avian body condition. Moreover, albumin, one of the main serum proteins, serves as the most favorable source of amino acids for synthesis of tissue proteins [30]. Similar total protein and albumin content in the blood of all the treatment groups in our study represented normal body condition of all the experimental groups.…”
Section: Blood Biochemical Parametersmentioning
confidence: 53%
“…The posthatch enhancing effects of IOF and EF, compared with the adverse effects of delayed first feeding, on muscle growth could be attributed to increased liver and muscle glycogen reserves , enhanced muscle protein synthesis (Yaman et al, 2000), accelerated development or better functionality of the small intestine (Tako et al, 2004;Smirnov et al, 2006;Foye et al, 2007), a higher reservoir of muscle progenitors (satellite cells; Halevy et al, 2000Halevy et al, , 2003Mozdziak et al, 2002a;Moore et al, 2005a,b), or their combination. Conceivably, adequate glycogen reserves and sufficient protein synthesis are crucial for higher functionality of the GIT, and hence for improved body and muscle growth.…”
Section: Discussionmentioning
confidence: 98%
“…Rajman et al (2006) reported that feed deprivation tended to decrease triacylglycerol, total plasma protein and cholesterol concentrations. Yaman et al (2000) described similar triacylglycerol pattern in growing feed-deprived chicks while plasma cholesterol was not influenced. Triacylglycerol concentration was decreased with travel distance at summer temperature (Vosmerova et al, 2010).…”
Section: Discussionmentioning
confidence: 66%